Is space a Global Common? - How declining international acceptance of the commons narrative applied to space limits its utility in the development of global space governance - Martinez, Peter; Johnson, Christopher D. (Frontiers in Space Technologies, 2026)
The notion of space as some sort of global common has been around since before the dawn of the Space Age and this notion has continued to be asserted by various commentators from time to time, most recently often in the context of space resource utilization. But, is space really a “global common” that “belongs” to all of humanity? This article discusses the concept of global commons as traditionally defined, understood, and applied on Earth. Then we review the evolution of commons-type language in multilateral documents and transpose the concept of the commons to the space domain, arguing that, while the freedom to engage in the activity of access and use outer space is a right held by all states under international space law, the domains of space themselves are not global commons or other such social constructs. Indeed, such constructs are mutable and not always correlated with peaceful, sustainable or prosperous uses of shared resources across history.